Pendampingan Usaha Bagi Tenaga Kerja Mandiri Pemula (TKMP) Kabupaten Pangandaran: Business Mentoring for Beginner Independent Workers (BIW) of Pangandaran Regency - Jaelani, Ihrom; Nur Jamiel, Harun; Acim, Acim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Beginner Independent Worker (BIW) mentoring program initiated by the Indonesian Ministry of Manpower is an effort to improve the quality and capacity of workers who have just started a business to compete in the market and develop their business independently. In its implementation, this program involves mentors tasked with guiding BIW in solving various aspects of their business problems, from recording business financial reports and marketing to obtaining a Business Identification Number (BIN). The partners in this mentoring activity are BIW in Pangandaran Regency, totaling 19 people. Mentoring activities are carried out offline and online through the stages of preparation, implementation of mentoring, and monitoring or evaluation. The mentoring results show that BIW can make notes on business financial reports, utilize social media to expand marketing reach, and have NIB as proof that the business that BIW runs is official/legal. Overall, this program seeks to create a sustainable entrepreneurial ecosystem, reduce unemployment and improve community welfare, and encourage inclusive economic growth, especially in Pangandaran Regency and generally in Indonesia.